Assessment of Nurses' Beliefs and Actions about Drug Addiction and Narcotics Safety - Nada Ahmd Hassn Shobily; Rawabi Mudhi Hezam Alrowais; Abdullah Abdu Naship Sharahili; Zahra Sami Almousa; Ashwag Yahya Kaabi; Inas Ahmed Hussein Moafa; Mashael Yahya Zbani; Amani Saad Alamri; Rawan Abdullah Abdukadir Hasan; Mohammed Awadhallah Zabin Aljuaid (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Evaluating nurses' attitudes and behaviors related to narcotic drug safety and addiction is essential for developing effective strategies to address substance abuse in healthcare settings. This study aimed to assess nurses' attitudes and behaviors concerning narcotic drug safety and addiction to inform health policies and promote patient and staff safety Methods: A mixed-methods study was conducted with 186 nurses at a general hospital. Data were collected through face-to-face interviews using a socio-demographic questionnaire, the Addictive Substance Attitude Scale, and open-ended questions. Quantitative data were analyzed using descriptive statistics, independent sample t-tests, one-way ANOVA tests, and regression analysis (p<0.001 and p<0.05). Qualitative data were analyzed thematically Results: The average age of participants was 35.62±7.95 years. While 82.8% of nurses reported following proper narcotic drug monitoring procedures, 61.3% were unaware of the protocol for managing healthcare professionals identified as substance abusers. The total mean score on the Addictive Substance Attitude Scale was 72.83±13.27. Significant differences were found between total scale scores and nurses' education level, drug monitoring status in their unit, addiction training, and routine use of drug disposal forms (p<0.05). Qualitative findings revealed themes of trust, support, normal working relationships, and acceptance towards addicted colleagues Conclusions: The findings highlight the importance of assessing nurses' attitudes and behaviors regarding narcotic drug safety and addiction. Nursing administrators should implement effective policies and strategies to ensure patient and staff safety and foster a supportive work environment